CREEP LIFE ASSESSMENT OF HIGH PRESSURE FEED WATER HEATER (HPFWH) SHELL AT COAL FIRED POWER PLANT - Alam, Hilman Syaeful; Djunaedi, Imam (Teknologi Indonesia, 2015)
The creep life of high pressure feed water heater shell of coal-fired power plant has been evaluated using the fitness for service (FFS) assessment based on creep rupture life calculation. The purpose of this study is to determine the remaining life of the component due to prolonged exposure to high operating temperatures and loading conditions. The assessment procedures consist of level 1, 2, and 3, the operating time which is evaluated based on the designed life of the components, i.e. 25 years. Based on the assessment results using level 1, total creep damage does not meet the requirements because the operating life is below the 25-year designed life, equal to 219,000 hours. However, based on the results of level 2 assessment, the component successfully achieves the design life with remaining life of 204,042 hours. These results are consistent with the assessment results obtained by level 3, but the remaining life of the component is only 6,806 hours after operated for 25 years.